To solve the equation \( \frac{8}{9}(x + \frac{1}{2}) = \frac{32}{3} \), follow these steps:
-
Multiply both sides by \( \frac{9}{8} \) to eliminate the fraction on the left side: \[ x + \frac{1}{2} = \frac{32}{3} \cdot \frac{9}{8} \]
-
Calculate \( \frac{32 \cdot 9}{3 \cdot 8} \):
- Divide \( 32 \) by \( 8 \) to get \( 4 \): \[ \frac{32}{8} = 4 \]
- Now multiply \( 4 \) by \( 9 \): \[ 4 \cdot 9 = 36 \] Thus, \[ x + \frac{1}{2} = 36 \]
-
Subtract \( \frac{1}{2} \) from both sides: \[ x = 36 - \frac{1}{2} \]
- Convert \( 36 \) into a fraction: \[ 36 = \frac{72}{2} \]
- Now perform the subtraction: \[ x = \frac{72}{2} - \frac{1}{2} = \frac{72 - 1}{2} = \frac{71}{2} \]
Therefore, the solution to the equation is: \[ x = \frac{71}{2} \]